Linear Relationship between Temperature and the Apparent Reaction Rate Constant of Hydroxyl Radical with 4-chlorobenzoic Acid. (4th May 2022) - Kawaguchi, Kohei; Hidaka, Taira; Nishimura, Fumitake
ABSTRACT: 4-Chlorobenzoic acid ( p -CBA) is frequently used as a hydroxyl radical (HO·) probe substance in studies of ozonation and advanced oxidation processes. However, the temperature dependence of the reaction between HO· and p -CBA remains unclear. In this context, we identified the relationship between temperature ( T, K) and the apparent second-order reaction rate constant of HO· with p - CBA ( k H O ⋅, p − C B A T, M −1 s −1 ): 10 10 . They were measured by a novel competitive method using 2-methylpropan-2-ol (tert-butyl alcohol) as a reference substance in the range of 1.0–40.0℃. The linear regression equation was more appropriate than the exponential regression equation to express this relationship. More generally, our simulation shows that the linear regression equation can be more accurate than the exponential regression equation to express the relationship between temperature and apparent reaction rate constants of HO.